Actions of Reconciliation - Tritter, Nicole Danielle Korenda (Arts, 2018)
This journey of R/reconciliation within myself, to this land and within this country has been a central theme of my research creation. I arrived on campus with questions about my role within the Canadian Reconciliation process and wondered whether I could make art to reflect R/reconciliation and/or create dialogue about its meaning. Using an Indigenous methodology that favours self-transformation, I used embodied knowledge to lead my art-making practice. University of Calgary/Mohkinstsis began as an art intervention on campus where I redesigned the University’s Coat of Arms and logo. The redesign was created though Indigenous traditional teachings, where “parallels” were found between oral and written knowledge systems. These “parallel practice” teachings became foundational thoughts for Stitching my flesh back together, a piece which reflects a more personal journey towards self-reconciliation. My cultural background has Mi’kmaq (from time immemorial), Acadian French (from the first colony in Canada) and Ukrainian immigrant (first-born Canadian) roots. These differing backgrounds often clashed within my body. I found reconciliation by using the traditional art-forms of cross-stitching, beading, quilling and quilting to create an interconnected image and complete person.